Residencias para adultos mayores: criterios básicos para su adecuada selección - Vergara R. , Sebastián (Revista Hospital Clínico Universidad de Chile, 2008)
In Chile, there exists limited knowledge about quantity and life conditions of old people living in nursing homes. Also, there may be insufficient supervision and directions on how to run a long stay residential. Lack of information may not facilitate the process of selecting a nursing home. Regarding this process, support and education for families attains great importance. As a way of providing information and promote the educative role of healthcare professionals, this document intends to provide general guidelines to considerate for an appropriate nursing home selection.